(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: This study aimed to assess the prevalence of anxiety and depression and to analyze associated factors among patients with acute myocardial infarction (AMI), serving as a basis for proposing appropriate psychological support strategies in nursing care. Methods: A cross-sectional study was conducted on 93 patients diagnosed with AMI who were receiving treatment at the Cardiology Center of Hong Ngoc – Phuc Truong Minh General Hospital. Results: Among the participants, 48.4% had clinically significant anxiety and 31.2% exhibited clinically significant depression. Notably, 29% of patients presented with both anxiety and depression. Factors significantly associated with these psychological disorders included gender, occupation, and health insurance status. Conclusions: A considerable proportion of patients with acute myocardial infarction experience anxiety and/or depression. Nursing care for these patients should include psychological assessment to promptly identify comorbid mental health issues and implement appropriate interventions, ultimately contributing to more effective patient management.